LUMUT SEJATI DI HUTAN ALAM PAMEUNGPEUK, TAMAN NASIONAL GUNUNG HALIMUN SALAK, JAWA BARAT [Mosses Pamengpeuk Primary Forest, Mount Halimun Salak Natiolan Park, West Java] - Windadri, Florentina Indah (Research Center for Biology-Indonesian Institute of Sciences, 2017)
Halimun Salak National Park is one of the remaining conservation areas left in West Java. Research on diversity of Bryophytes had previously been conducted at Halimun Mount, Kendeng Mount and the lowland forest surrounding Cikaniki-Citalahab, while this present study was aimed to record the diversity of mosses at Pameungpeuk primary forest. There were 78 species of mosses including in 47 genera and 20 families. Syrrhopodon spiculosus Hook. & Grev. was a dominant species in the research area. Twenty seven species were new record for Halimun Salak National Park, one of which (Rhizogonium lamii Reimers) was a new record for Java and seven species were new record for Indonesia.